MITIGASI JUDI ONLINE MELALUI PENDEKATAN AGAMA ISLAM - Kuryani Kuryani; Aria Septi Anggaira; Muhammad Hafidz Khusnadin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The phenomenon of online gambling is becoming increasingly widespread and has a negative impact on the economic, social, and moral aspects of society. In Islam, gambling (maisir) is strictly prohibited because it involves elements of harm, uncertainty, and injustice. This study aims to examine mitigation strategies for online gambling through an Islamic values approach. The method used is a literature review with a qualitative approach. The findings indicate that a religious approach, particularly Islamic values, can provide preventive and curative solutions to gambling behavior, including through religious education, the role of religious leaders, and strengthening faith and community-based social control. Therefore, spiritual and moral approaches must be integrated into efforts to address online gambling in society.